2020
DOI: 10.1101/2020.08.03.20167254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review of Forecasting Models for Coronavirus (COVID-19) Pandemic in India during Country-wise Lockdowns

Abstract: COVID-19 is spreading widely across the globe right now. Majority of the countries are relying on models and studies such as stochastic simulations, AceMod model, neural networks-based models, exponential growth model,Weibull distribution model, and so on to forecast the number of COVID-19 cases in the coming months. The objective on utilizing these models is to ensure that strict measures can be enacted to contain the virus spread and also predict the resources required to deal with the pandemic as the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Building upon the previous research [18], current study implemented two numerical models to forecast the number of cases related to COVID-19 in India, namely – exponential curve fitting and least square fitted model. Both of the models forecasted an upward of 30 lakhs cases and 40,000 deaths for the upcoming months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building upon the previous research [18], current study implemented two numerical models to forecast the number of cases related to COVID-19 in India, namely – exponential curve fitting and least square fitted model. Both of the models forecasted an upward of 30 lakhs cases and 40,000 deaths for the upcoming months.…”
Section: Resultsmentioning
confidence: 99%
“…Short-term forecasting can be done based on elementary analytical approaches instead of diving into complex architectures like disease modelling or neural networks. Previous research [18] has shown that for shorter durations, simplistic curve fitting models achieve better accuracy than regression and pandemic models. Observing the patterns of number cases in countries such as China, Spain and Italy we can infer that the natural infection rate curve will follow a non-linear path initially till it hits its peak and begins to subside.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several of these reviews offer a categorization of the different models with a precise terminology [3,4,1] or a mapping of the articles with their key features [5,3]. Since November 2020, we can mention many projects of the latter type focusing on the COVID-19 epidemic, including published reviews [6,7,8] and continuously updated works of scientific watch [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Some have focused on evaluating model performance on their weekly cumulative predictions. For instance, two different studies (5, 6) assessed the performance of different models with the median absolute percent error (MAPE) of cumulative deaths. Fried-man et al (5), observed that the calculated MAPE increased for longer forecasts, and the best performance model varied by region.…”
Section: Introductionmentioning
confidence: 99%